2020
DOI: 10.1093/brain/awaa099
|View full text |Cite
|
Sign up to set email alerts
|

Janus-faced spatacsin (SPG11): involvement in neurodevelopment and multisystem neurodegeneration

Abstract: Hereditary spastic paraplegia (HSP) is a heterogeneous group of rare motor neuron disorders characterized by progressive weakness and spasticity of the lower limbs. HSP type 11 (SPG11-HSP) is linked to pathogenic variants in the SPG11 gene and it represents the most frequent form of complex autosomal recessive HSP. The majority of SPG11-HSP patients exhibit additional neurological symptoms such as cognitive decline, thin corpus callosum, and peripheral neuropathy. Yet, the mechanisms of SPG11-linked spectrum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 76 publications
2
24
0
Order By: Relevance
“…Previous studies reported an accumulation of autophagosomes in SPG11, due to a deficit in autophagolysosome reformation ( Renvoisé et al, 2014 ; Branchu et al, 2017 ; Vantaggiato et al, 2019 ; Pozner et al, 2020 ; Khundadze et al, 2021 ). Ultrastructural analysis of SPG11 MNs confirmed this finding, revealing presence of neuritic electron-dense aggregates in SPG11, but not in control MN neurites which exhibited small electron dense lipofuscin particles only ( Figures 2C,D and Supplementary Figure 2C ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies reported an accumulation of autophagosomes in SPG11, due to a deficit in autophagolysosome reformation ( Renvoisé et al, 2014 ; Branchu et al, 2017 ; Vantaggiato et al, 2019 ; Pozner et al, 2020 ; Khundadze et al, 2021 ). Ultrastructural analysis of SPG11 MNs confirmed this finding, revealing presence of neuritic electron-dense aggregates in SPG11, but not in control MN neurites which exhibited small electron dense lipofuscin particles only ( Figures 2C,D and Supplementary Figure 2C ).…”
Section: Resultsmentioning
confidence: 91%
“…Mitochondrial dysfunction and impaired transport of mitochondria have been implicated in various neurodegenerative diseases including Charcot-Marie Tooth 2A and Parkinson's (Kitada et al, 1998;Palacino et al, 2004;Lezi and Swerdlow, 2012;Stevens et al, 2015;Rizzo et al, 2016;Prots et al, 2018). Interestingly, increasing evidence supports a specific vulnerability of dopaminergic neurons in SPG11 (Paisan-Ruiz et al, 2010;Guidubaldi et al, 2011;Faber et al, 2018b;Pozner et al, 2020).…”
Section: Overlapping Disease Mechanisms In Spg11 and Spg15mentioning
confidence: 99%
See 1 more Smart Citation
“…However, miglustat poorly crosses the blood–brain barrier and it would be informative to test whether an alternative strategy to decrease ganglioside levels in the brains of Spg11 knockout mice can improve the motor or cognitive symptoms that have been observed 86 . As SPG11 patients generally present their first symptoms before 10 years of age, it has been proposed that aside from neurodegeneration, altered brain development may contribute to the disease 87 . Consistent with this hypothesis, models derived from induced pluripotent stem cells of SPG11 patients show reduced proliferation of neuronal progenitors, impaired neurogenesis, and impaired neuronal differentiation 88 , 89 .…”
Section: Management Of Hspmentioning
confidence: 99%
“…HSPs are characterized by spasticity and weakness of hip and leg muscles that are caused by axonal degeneration of cortical motor neurons. HSP patientspecific iPSC lines were generated for multiple form of HSP including SPG4 [116,117], SPG3A [118], SPG11 [119,120], SPG15 and SPG48 [121]. By knocking in disease-related mutations using gene editing, disease-specific phenotypes were recapitulated, providing additional models to study HSPs [122].…”
Section: Other Motor Neuron Diseasesmentioning
confidence: 99%